Sedentarism in Costa Rican children: yes, there is a solution - Álvarez Bogantes, Carlos (2006)
The purpose of this article was to review the nature of physical activity patterns of children in order to relate them to the recommendations provided regarding the physical activity that children must have.  Additionally, these recommendations are compared to what has been done traditionally in Costa Rica.  In another section of the article, games are mentioned as an alternative for making movement fun for children and creating active lifestyles mainly using physical education classes.